REVISITING THE DETERMINANTS OF STUDENTS’ SUCCESS IN CONDUCTING CREATIVITY PROGRAM - Sumaryanto Sumaryanto; Tchello Kasse; Nur Hidayanto Pancoro Setyo Putro (LPMPP Universitas Negeri Yogyakarta, 2019)
This study investigated the determinants of students’ success in completing creativity programs. A survey design was used in this study. A total of 351 respondents completed a survey on the factors that theoretically were related to students’ creativity. Exploratory factor analysis (EFA) was then conducted to explore the factors that emerge as the correlates of students self-efficacy in completing the creativity program. Subsequently, confirmatory factor analysis (CFA) was performed to confirm the pattern proposed in the EFA. Finally, Structural Equation Modelling with Mplus was conducted to explore how the factors are related to students self-efficacy in completing the creativity program. The results showed that students’ self-efficacy are strongly related to the role of their advisors, supports from their research community, and supports from the university. Comprehensive discussions on these factors are provided throughout this paper.